In-situ Investigation of the Oil-Water Interface Under Dynamic Conditions - Hyde, Anita Evelyn (Curtin University, 2018)
This thesis describes the development of a new technique targeting interfacial measurements of liquid-liquid systems in practical scenarios: movement in the sample, low Bond number systems or systems which are physically constrained. A holm meridian is formed around a submerged sphere, producing an axisymmetric interface with pronounced curvature to which shape-fitting methodologies are applied. The technique has been used successfully in three dynamic conditions: microwave heating, magnetization and chemical reactions.